Effect of selenium and vitamin E supplementation during late pregnancy on colostrum and plasma Se, Cu, Zn and Fe concentrations of fat tail Sanjabi ewes and their lambs - M.T. JALILIAN; M.M. MOEINI; K. KARKODI (Acta Agriculturae Slovenica)
Twenty seven fat tail ewes were randomly assigned to three treatment groups. Four and two weeks before expected lambing, ewes were injected intramuscularly 0 ml (C) 5 ml (T1), 10 ml (T2) selenium and vitamin E respectively. Blood samples were collected from ewes four weeks before expected lambing and on the day of lambing. Blood samples of their lambs were taken from the jugular vein at birth and 7 days of age. Selenium, copper, zinc and iron concentrations of plasma and colostrum were measured by inductively couple plasma (ICP-OES). The plasma Se concentration of lambs in T2 was significantly increased compared with control group at 7 days of age (P < 0.05). The colostrums Se and Cu concentrations were significantly increased in Se supplemented ewe and their lambs (P < 0.05). The plasma Zn concentration of ewes at lambing and colostrum were significantly decreased in T2 compared with controls. The plasma Zn concentration of lambs of ewes of T2 was significantly decreased compared with other groups at 7 days of age (P < 0.05). The serum concentration of Cu increased in supplemented ewes, which was concomitant with a reduction in Zn concentration in serum and colostrums. It seems that an increase in serum concentration of Cu at the end of pregnancy in ewes given Se supplement could disturb the Zn: Cu ratios which in turn lead to Zn reduction. There was a positive correlation between serum Se concentration with Cu and Fe levels and also a negative correlation between Se and Zn in treated ewes.